Teachers’ Challenges in Teaching Basic English Literacy in Multicultural and Inclusive Classroom - Kadek Diah Nilawati; Ni Nyoman Padmadewi; Kadek Sintya Dewi (MAN 4 Kota Pekanbaru, 2026)
This study aims to examine the challenges faced by teachers in teaching basic English literacy through the Montessori method in multicultural and inclusive classroom. A qualitative approach with a case study design was used in this study. This research was conducted at Singaraja Montessori School and in the Octopus class. Two teachers who teach in the Octopus class were participants in this study. Research data were collected through observation, semi-structured interviews, and document analysis, which were then analyzed using the Miles and Huberman model. Based on data obtained from two purposively selected teachers who were directly responsible for teaching basic English literacy in the Octopus class, the findings of this study indicate three challenges faced by teachers when teaching basic English literacy through the Montessori method. First, the challenge of differences in student literacy levels because the Octopus class consists of grades 1-3 and a diverse student body. Second, the challenge of accommodating students with special needs, especially in providing individual support, simple instructions, and visual aids while maintaining a conducive classroom environment. Third, the difficulty in developing flexible lesson guides to respond to the various differences that exist in students. This research shows that teaching basic English literacy through the Montessori method in multicultural and inclusive classroom requires continuous observation, flexible planning, and balanced support to ensure all students can participate without exception and according to their individual abilities.